From the Golden Rectangle to the Fibonacci Sequences - Liba, Opher; Ilany, Bat-Sheva. (Cham : Springer International Publishing : Imprint: Springer, 2023)
The book takes us on a fascinating journey through one of the most beautiful and fascinating topics of mathematics. It presents a wealth of information about the golden ratio and the Fibonacci sequence. The book introduces the reader to novel perspectives to classic mathematical concepts and problems. The book's structure engages with the reader actively, leading to more profound understanding, satisfaction and deep insights in learning mathematics. The book strengthens and expands the readers' mathematical knowledge, allowing them a glimpse of several advanced academic concepts. It demonstrates and instils the essence of mathematical research, along the lines of George Polya: observation, conjecture, proof, implementation, generalization and raising new questions.
Chapter 1 Introduction -- 2 The Golden Rectangle and the Golden Ratio -- 3 Introducing Golden Triangles -- 4 The Fibonacci Sequence -- 5 The Lucas Sequence -- 6 The General Fibonacci-like Sequences -- 7 List of Formulas, Theorems, and Definitions.
Keywords: Mathematics; Teachers -- Training of; Learning, Psychology of; Education -- Research; Mathematics Education; Teaching and Teacher Education; Learning Theory; Research Methods in Education